Implications of SARS‐CoV‐2 on current and future operation and management of wastewater systems. (6th October 2020) - Maal‐Bared, Rasha; Brisolara, Kari; Munakata, Naoko; Bibby, Kyle; Gerba, Charles; Sobsey, Mark; Schaefer, Scott; Swift, Jay; Gary, Lee; Sherchan, Samendra; Babatola, Akin; Bastian, Robert; et al.
Abstract: While researchers have acknowledged the potential role of environmental scientists, engineers, and industrial hygienists during this pandemic, the role of the water utility professional is often overlooked. The wastewater sector is critical to public health protection and employs collection and treatment system workers who perform tasks with high potential for exposures to biological agents. While various technical guidances and reports have initially provided direction to the water sector, the rapidly growing body of research publications necessitates the constant review of these papers and data synthesis. This paper presents the latest findings and highlights their implications from a water and wastewater utility operation and management perspective. Practitioner points: Extrapolation from SARS‐CoV‐1 and MERS‐CoV, as well as other surrogates, has helped predicting SARS‐CoV‐2 behavior and risk management. Data from treated wastewater effluent suggest that current processes are sufficient for SARS‐CoV‐2 control. Scientific evidence supports the  possibility  of fecal–oral transmission for SARS‐CoV‐2. Limited evidence supports the potential survival of infective SARS‐CoV‐2 on surfaces and in aerosols and the efficacy of control measures at reducing transmission. Protective practices and PPE can protect workers from SARS‐CoV‐2 and other pathogens found in wastewater. Abstract : Factors influencing SARS‐CoV‐2 Risk Management and Mitigation at Water Resource Recovery Facilities.